Performance budgeting in context: An analysis of Italian central administrations - Andrea Bonomi Savignon; Lorenzo Costumato; Benedetta Marchese (Administrative Sciences, 2019)
The impact of financial austerity in many countries and the need to set the direction for governments have radically changed several aspects of Public sector management (Rubin and Willoughby 2014; Anessi-Pessina et al. 2016). A central component of this effort to transform public management involves using strategic planning and performance measures for budgeting decisions (Joyce 1997). Over the last decade, there has been an increase in the use of performance budgeting at the national as well as at subnational and local level, with varying approaches and results across countries (Bleyen et al. 2017; OECD 2017). This article analyzes the dynamics of strategic planning and performance management practices in relation to the budgeting processes in the context of the Italian central government, with the aim of evaluating whether a predominant integration model is apparent in relation to those used in different countries at the OECD level. Starting in 2009, reforms concerning the implementation of performance management tools in the Italian public sector have been promoted and revised, although the need to fully integrate the performance and budgeting processes looks urgent. Based on data from Italian Ministries, this article analyzes the type of relationship and the degree of coherence between adopted strategic plans and budgets. The results show the persistence of a prevalent misalignment between planning and budgeting. Data that were collected from the analysis of strategic plans and budgets from ten Ministries depict a patchy situation, in which some ministries integrate the processes defining a consistent and comparable model, while some others do not. In the conclusions, areas for improvement of the process are identified, while providing policy implications.
Keywords: 350; strategic management; performance management; performance-based budgeting